RARE THORACOPULMONARY NEOPLASM IN A YOUNG FEMALE: A CASE REPORT. - Sumera Batool; Ashok Panjwani; Amenah Jafarey; Nadeem Rizvi (ziauddin University, 2019)
Fusion of two teeth is rare developmental disorder which is encountered by a clinician. It is commonly reported in deciduous dentition. The fused crown appears broader and usually an esthetic concern. This condition usually reveals a decreased teeth count. Unilateral occurrence of fusion in permanent mandibular anterior teeth is a rare phenomenon. Hence this case report is presented.